Diagnóstico da piscicultura na agricultura familiar dos municípios de Toledo-PR e Maripá-PR - Debus, Dieterson (2016)
Family farming is configured as an important strategy for sustainable rural development, food production, job creation and community building and productive practices. In this context, the cities of Toledo and Maripá have increased both in fish production and productivity. Toledo is the first state of the producer in the fish farming sector with a production of about 50 million fry and about six million kilos of fish killed in 2015. But the municipality of Maripá in addition to the production there are the productivity. There are 89 fish farmers, who cultivate an area of about 125.0 ha of water surface, with an average yield of 7.0 t/ha, while the state average is about 2.5 t/ha. As such, good management of small rural property is of great importance for both tax requirements as to the knowledge of the results of the activity. Balance sheets, income statements and other reports based on rural accounting tools are of paramount importance for property management. Thus, this thesis analyzed the financial control of the activity of fish farming in family farming in the cities of Toledo and Maripá in the west of Paraná, listing the aspects of family farming, sustainable development and management real estate. Therefore, on the basis of documentary literature interviews, literature and field-directed fish farmers Toledana Aquaculture Association - Atoaqui and the Association of Aquaculture Aquaculture Producers - Aquimap. The results highlighted the low level of education of fish farmers, a greater financial dependence on activity by Maripá fish farmers, lack of effective financial control in the activity, the situation has an impact development of strategies and future investment. Also noteworthy are the weak provision of technical assistance by associations and the highest percentage of issuance of producer tax notes among Maripá fish farmers. As far as the environmental aspects are concerned, most of the properties comply with the legislation in force. In addition, there is no effective treatment of effluent produced by fish farms in both cities. In addition, research has shown the importance that activity on the income of the families surveyed, which contributes to the improvement of the quality of life of these. However, the major challenge in dealing with this same time, with all the daily financial, political and environmental activities and still manage related to rural properties. Thus, it is expected that this research will contribute to future studies, as well as contribute to the development of family farming, which has an important role in the development of cities and the country